Selecting a method for reducing friction in rotary refrigeration compressors developed for import substitution - N. A. Kudla; A. V. Burakov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses one of the methods for reducing friction, used for newly developed rotary compressors as part of import substitution work. The experience of using rotary refrigeration compressors is analyzed and the main factors determining refrigeration capacity are identified. Methods used in aerospace engineering and power engineering to reduce friction and increase the service life of mechanical elements and assemblies using metallic and non-metallic materials have been identified, and the most promising materials and development trends have been analyzed. A fairly common method of reducing friction, based on the weariness effect, is chosen for study. Based on already known results, a technical solution based on the wear-free effect has been proposed to reduce friction of a refrigeration compressor with a rolling rotor.